Analysis of volatile organic compounds and metabolites of three cultivars of asparagus (Asparagus officinalis L.) using E-nose, GC-IMS, and LC-MS/MS. Issue 4 (1st April 2022) - Yang, Chun; Ye, Zheng; Mao, Liping; Zhang, Ling; Zhang, Jiangning; Ding, Weiying; Han, Jiming; Mao, Kai
ABSTRACT: Asparagus ( A. officinalis L.) is a perennial herb of the genus Asparagus that is rich in nutrients. This study aimed to distinguish three cultivars of asparagus (Paladin, Grace, and Jinggang red) based on their volatile organic compounds (VOCs) and metabolic profiles. VOCs in the three cultivars were separated and identified using electronic nose (E-nose) and gas chromatography–ion mobility spectrometry (GC–IMS). Differences in metabolites among the three cultivars were analyzed using liquid chromatography-tandem mass spectrometry (LC-MS/MS). E-nose and GC-IMS showed that the VOCs in asparagus differed significantly among the three groups. E-nose result showed that purple asparagus (Jinggang red) was connected to a stronger earthy odor; green asparagus (Paladin and Grace) were shown characteristic dill flavor. Moreover, 50 VOCs were detected by using GC–IMS. Ketones and alcohols were most abundant in Paladin; methyl benzoate and dimethyl sulfide were most abundance in Grace; aldehydes and acids were most abundance in Jinggang red. Moreover, 130 and 71 different metabolites were detected in the positive and negative modes among three cultivars, such as quercetin and rutin. Functional analysis revealed that these metabolites were involved in beta-alanine metabolism and ATP-binding cassette (ABC) transporters. In summary, E-nose combined with GC-IMS and LC-MS/MS methods has good application prospects in evaluating and identifying VOCs and metabolites of different cultivars of asparagus. The identified VOCs and metabolites can provide guidelines for the development of functional asparagus products. GRAPHICAL ABSTRACT: uf0001